CPEC and Pakistan’s Debt Dynamics: Myth or Reality of a Debt Trap - Arsalan (Journal of Development and Social Sciences, 2025)
This research evaluates the extent to which the China-Pakistan Economic Corridor (CPEC) contributes to Pakistan’s debt Burden. It also assesses the extent to which the debt burden might be related to CPEC and aims to assess the validity of claims that CPEC is a major cause of Pakistan’s rising debt. The study has a secondary aim to explore the underlying causes of Pakistan’s longstanding debt problem. CPEC, an important part of China’s Belt and Road Initiative, is seen by some as a potential debt trap for Pakistan. However, the debt problems plaguing Pakistan predate CPEC and stem instead from a number of long-standing systemic issues—like stagnant economic growth, low revenue generation, and poor fiscal management. Despite the critique, CPEC has the potential to greatly improve Pakistan’s infrastructure, energy, and overall economic development. This qualitative research undertakes a longitudinal analysis of Pakistan’s economic performance (2013-2023) and the debt profiling of CPEC projects. The study is primarily informed by data from international agencies and authorities that oversee CPEC. This is supplemented by a variety of secondary, scholarly, and otherwise-publicly-available resources. Results indicate that 80% of CPEC initiatives are equity-based, with a minimal burden of debt on the government. The financing modalities of grants, concessional loans, and private investments contradict the debt-trap narrative. The real problem is that Pakistan has a pre-existing economic structural problems like fiscal deficit, which has led it to debt trap. Pakistan needs to carry out fiscal reforms, improve governance, broaden the export base, and optimize the potential of the China-Pakistan Economic Corridor (CPEC) to achieve sustainable development and solve its debt problems.